What are your blind spots? : conquering the 5 misconceptions that hold leaders back - Haudan, Jim; Berens, Rich (McGraw Hill-Ascent Audio, 2018)
Uncover your blind spots and reset your leadership approach for long-lasting success in any business Far too many business leaders today are using outdated practices to engage and motivate their people-and they're failing miserably. Truly resilient, thriving organizations are those that are purpose driven and focus on more than pure profits. Purpose, or an underlying company philosophy, not only drives strategic change, but also encourages customer loyalty and employee engagement. In order to succeed, leaders must be willing to discard old ways of thinking and detrimental business habits-and recognize their blind spots. Authors Jim Haudan and Rich Berens identify the five most common leadership blind spots that hamper success: Purpose, Story, Engagement, Trust, and Truth. They take you straight into the board room of well-known leadership teams to illustrate how these blind spots play out and the impact they have on organizations. You'll learn how to identify and overcome your own blind spots and embrace positive, forward-thinking new practices. What Are Your Blind Spots equips you with the tools needed for a personal leadership reset. You'll discover how to increase engagement, productivity, and growth in your own organization. This is an invaluable guide for executives, managers, team leaders, and human resource professionals looking for an effective way to engage and motivate employees at every level of an organization.